Plakophilin 1 deﬁciency in prostatic tumours is correlated with immune cell recruitment and controls theup-regulation of cytokine expression post-transcriptionally - Kim, Martin; Reidenbach, Sonja; Schlechter, Tanja; Rothmann, Ann Christin; Will, Rainer D.; Hofmann, Ilse (The FEBS journal, 2023)
Plakophilin (PKP1) 1 is a member of the arm-repeat family of catenins and acts as a structural component of desmosomes, which are important stabilizers of cell–cell adhesion. Besides this, PKP1 also occurs in a non-junctional, cytoplasmic form contributing to post-transcriptional regulation of gene expression. Moreover, PKP1 is expressed in the prostate epithelium but its expression is frequently downregulated in prostate cancers with a more aggressive phenotype. This observation may imply a tumour-suppressive role of PKP1. We found that, in prostatic adenocarcinomas with PKP1 deficiency, the occurrence of T-cells, B-cells, macrophages and neutrophils were significantly increased. In a PKP1-deficient prostatic cancer cell line expressing IL8, these levels were statistically meaningfully reduced upon PKP1 re-expression. When analysing prostatic PKP1 knockdown cell lines, the mRNA and protein levels of additional cytokines, namely CXCL1 and IL6, were upregulated. The effect was rescued upon re-expression of a PKP1 RNAi-resistant form. The corresponding mRNAs were co-precipitated with cytoplasmic PKP1, indicating that they are components of PKP1-containing mRNA ribonucleoprotein particles. Moreover, the mRNA half-lives of CXCL1, IL8 and IL6 were significantly increased in PKP1-deficient cells, showing that these mRNAs were stabilized by PKP1. In an in vitro migration assay, the higher cytokine concentrations led to higher migration rates of THP1 and PBMC cells. This finding implies that PKP1 loss of expression in vivo correlates with the recruitment of immune cells into the tumour area to set up a tumour-specific environment. One may speculate that this newly established tumour environment has tumour-suppressive characteristics and thereby accelerates tumour progression and metastasis.
Online veröffentlicht: 15 November 2022